Angiographic Evaluation of TMI 3 Flow (Normal Flow) in STEMI Patients Undergoing Primary PCI at Tertiary Cardiac Care Centre - Yawar Abbas, !wan Illahi Soomro, Abdul Mueed, Haroon Ishaque, Qurban Ali Rahu, Riaz Ahmed Mangi , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine the frequency of TIMI 3 flow rates in ST segment elevation myocardial infarction patients undergoing Primary PCI. Methods: This cross sectional study was conducted in the Department of Cardiology, National Institute of Cardiovascular Diseases(NICVD) at Karachi during April 2014 to October 2014 by using convenience sampling technique. This study includesl 69 study subjects of either gender having age between 35-75 years, presented with chest pain were included. Patients were moved to Cath lab where primary PCI was done to accomplish TIMI flow grade 3 and the descriptive data was calculated and statistically analyzed. Results: There were 127 (75.14%) male and 42 (24.86%) female patients with mean age group 57.31±10.58. Among all, 9.5% patients had symptoms since 60 minutes, 14.2% since 90 minutes, 32.0% since 120 minutes, and 44.4% patients had symptoms since >120 minutes. TIMI flow of grade 3 after PCI was achieved in 127(75.1 %) patients. No significant association of TIMI flow grade 3 was observed with gender, age, hypertension, diabetes, smoking, and ECG diagnosis (p>0.05). Conclusion: STEMI cases treated by primary PCI, TIMI-3 flow grade was accomplished in about 75% of cases with the door-to-balloon time a key factor.